The social and temporal construction of climate change. A comparative study of The Guardian and Washington Times newspapers - Căpățână, Octavian-Mihai (Journal of comparative research in anthropology and sociology, 2024)
This study examines how media outlets with opposing political orientations construct different temporal narratives around climate change. Through a comparative content analysis of The Guardian and Washington Times’ online platforms, I analyze how these newspapers use time as a rhetorical device to shape the public understanding of climate change. The analysis reveals distinct temporal frameworks: The Guardian emphasizes urgent future threats and immediate action, while Washington Times employs past-oriented narratives to minimize climate concerns. These contrasting temporal constructions reflect broader ideological divisions and demonstrate how media outlets use time work to support their political perspectives on climate change. The findings contribute to our understanding of how temporal framing in media discourse influences public perception of environmental issues.